Analysis of the Impact of Problem-Based Learning on Student Learning Styles - Putri Puspita Sari; Diyah Nurhayati (International Journal of Mathematics and Science Education, 2024)
This study aims to analyze the impact of problem-based learning on student learning styles. The research approach used is experimental by adopting observation and questionnaire methods. Data was collected from students who engaged in problem-based learning and students who followed conventional learning approaches. Analysis was carried out to compare differences in student learning styles before and after implementing problem-based learning. The results showed that problem-based learning had a significant impact on changes in students' learning styles, with more students tending to adopt active, collaborative, and reflective learning styles.